Contrarian and Momentum Strategies in Malaysia - Yap, Jia Huey (2010)
This study aims to test the profitability of contrarian and momentum strategies in the Malaysian stock market over the period of 1990 to 2010 and the sub-periods which include two normal period and two crisis periods. Results show that for the full period, the Malaysian market exhibit contrarian profits for the 3 months to 4 years period and momentum profit for the five years period. This suggests medium to long term price reversal and long term price continuation. The sub-period analysis shows similar profitability for the two normal periods and the Asian Financial Crisis. However, the tests on the current Global Financial Crisis provide mixed results with no clear success of either strategy. The decomposition of the contrarian and momentum profits found that the major source of contrarian and momentum profits is attributed to the idiosyncratic component of stock returns and not due to systematic factors, implying potential market inefficiencies. Further analysis indicates that high beta is not the source of momentum and contrarian profit. This study also found no evidence of January nor February effect in the Malaysian stock market.